Pemanfaatan Rubrik Sebagai Instrumen Penilaian Alternatif - Wiyun Philipus Tangkin (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2019)
This research aims at describing clearly about the contribution of using rubric as alternative assessment towards students learning motivation. This research was conducted at Dian Harapan Karawaci in grade IX junior high school. This is a descriptive qualitative research, the data collection uses interview, questionnaire, and documents. The interview involved five science teachers (who teach physics, biology, and chemistry) and 15 students of grade IX. The data in the form of questionnaire were gathered from teachers and students, analyzed by using statistic in order to obtain the percentage of answer from the teachers and students. It is concluded that the rubric of assessment has close relationship with students learning motivation. In its contribution, rubric as a means of assessment is able to motivate students learning.